Sentidos e significados da negritude no Maracatu Nação Iracema - Cruz, Danielle Maia (2008)
This work aims to ponder about the meanings of black identity into identities formulation and/or re-signification by the “Maracatu Nação Iracema” members, situated in Fortaleza, Ceará State. Specifically, how these symbolic configurations act over maracatu´s choreographies, loas, dressings and storyline elaboration, chiefly in Carnival parade that happens at Domingos Olímpio avenue. The identity concept is understood as fluid, not essential, not homogenous and according to Carneiro da Cunha terms, as a difference strategy, into a situational and relational perspective. I, therefore, perform an ethnography of these events, that envelop maracatu Nação Iracema members, understanding their presentations, reunions and others activities, such as ritualistic moments that express social messages into a very impetuous way, chiefly the ones related to the black identity, what allows one to comprehend the motive by which part of the players considerate Nação Iracema as the maracatu who represents the black people at Ceará. Thus, the research presents maracatu as an energetic instrument of identity affirmation of directors and some of it´s members and, in this way, as a space for the construction of black men identity. Field data also clarify the present diversity into maracatu, thus deconstructing the idea of a bonded, essential and homogenous group. By this way, I speak about subjects that make themselves present into maracatu because of motivations far from blackness; those who do not recognize themselves as black people, but that in some moments call themselves as so and in other occasions deny this identity, as well as those who recognize themselves as black people and because of this elaborate or take part into political actions. So, the discussions do not take hold in finding only one way to be black, but yet in distinct forms of sharing this belonging; different forms of feeling a black person; distinct ways to live this identity.